Mechanical, workability, economic and environmental properties of concrete with limestone calcined clay cement and recycled aggregates - Yong Yu; Mingjian Yang; Cheng Wan; Lang Lin (Scientific Reports)
Abstract Limestone calcined clay cement (LC3) and recycled aggregates (RAs) are important innovations in civil engineering, offering solutions to the industry’s energy and carbon challenges. However, limited research on their combined use has hindered widespread application. This study systematically evaluates LC3-based concrete with both coarse and fine RAs, using material testing, cost analysis and carbon footprint assessments to examine the effects of water-to-binder ratio, metakaolin-limestone powder synergy, RA content and particle quality on workability, compressive strength, elastic modulus, splitting-tensile strength, unit cost and environmental impact, while establishing clear quantitative relationships. Key findings include: (i) Using up to 50% metakaolin-limestone powder by mass, 30% coarse RA and 20% recycled sand by volume results in minimal reductions in 28-day strength and elastic modulus. However, exceeding 70%, 50% and 40%, respectively, leads to significant mechanical deterioration. (ii) LC3 concrete has 4-15% lower strength than Portland cement concrete at 14 days due to slower pozzolanic reactions, but strength levels equalize by 28 days. Similarly, recycled aggregate concrete shows lower early-age strength, with extended curing further highlighting performance differences, likely due to the residual mortar on recycled particles. (iii) Lifecycle analysis confirms that replacing 50% of the binder with metakaolin-limestone powder reduces carbon emissions by 29.9% and costs by 12.4% for strength-equivalent concrete. In contrast, RAs offer only modest sustainability benefits, with 20% recycled sand and 30% coarse RA increasing emissions by 5.4% and 2.8%, respectively, while keeping costs stable. (iv) The quality of RA particles plays a key role in their sustainable application. Additionally, transportation distance significantly affects the circular benefits of RA use but has a limited impact on the sustainability of metakaolin-limestone powder.